The biophysical potential for urea deep placement technology in lowland rice production systems of Ghana and Senegal - Cox, Cindy M.; Kwon, Ho Young; Koo, Jawoo (International Food Policy Research Institute, 2015)
The application of nitrogen (N) fertilizers is still insufficient across cropping systems in Africa south of the Sahara, while plant uptake of nitrogen is often inefficient and wasteful even when farmers apply fertilizers. This leaves sizable room for improving the productivity of crops and managing nutrient cycles. Fertilizer deep placement is a technology designed to enhance the efficiency of nutrient delivery to crops by placing granulated fertilizer directly in the root zone. Deep placement maximizes nutrient uptake by crops while using less fertilizer than surface broadcasting, and minimizes N losses due to runoff and ammonia volatilization. Urea deep placement (UDP) technology has been widely adopted in lowland paddy rice production systems in South Asia, especially in Bangladesh. There is a growing interest to scale up UDP adoption in West African countries, such as Ghana and Senegal, but a limited number of studies have been published from the region to support developing strategies. To contribute to the evidence-base, we use a grid-based cropping systems modeling framework, combined with analyses on the characterization of UDP and its geospatial targeting, and map the extent of biophysical suitability for UDP across regions in Ghana and Senegal and estimate potential yield increases under this technology.